Comparing the Effectiveness of Group Schema Therapy and Cognitive Bias Modification on Test Anxiety in Male Students - Morteza Ataei; Ali Pakizeh; Yousef Dehghani; Fariba Cheraghi (Shiraz University of Medical Sciences, 2024)
Background: Many individuals, particularly adolescents, often deal with anxiety which in turn impacts their environmental perception. The present study aimed to compare the effectiveness of group schema therapy and cognitive bias modification (CBM) on test anxiety in high school male adolescents.Method: This was a semi-experimental study with a pre-test and post-test design, two experimental groups, and a control group. The statistical population included all male high school students of Abadan, Iran in the academic year of 2020-2023. A total number of 45 people were selected using the convenience sampling method from secondary high schools in Abadan, Iran. Fortyfive students were assigned into two experimental groups and a control group (15 students in each group). The first experimental group received schema therapy (eight 90-minute sessions; one session every week) and the second experimental group received cognitive bias modification (eight 20-minute sessions; two sessions every week). The control group was considered on the waiting list. The General Self-Efficacy Scale was used for data collection. The tools used were Ahvaz Test Anxiety Inventory )ATI) and Probe Dot Task (PDT). SPSS version 25 was applied to analyze covariance.Results: Most of the participants were mathematics (64%) and a tenth grade (62%) students. The study results showed a significant difference between Schema Therapy, CBM, and control groups in test anxiety based on the pre-test and pre-test scores (P=0.001). Also, the experimental and control groups had significant differences in reaction time and attentional bias based on the pre-test and pre-test scores (P=0.001, P=0.025, P=0.038, P=0.026). The Schema Therapy and CBM groups also showed a significant difference between pre-test and post-test observations (P=0.001). However, no difference was found in the control group based on pre-test and post-test scores (P=0.054, P=0.424, P=0.709, P=0.066).Conclusions: Schema therapy and CBM groups showed a significant difference in test anxiety between the pre-test and post-test observations. However, no difference was found in the control group. Given the pre- and post-test scores, the CBM experimental group and the control group showed significant differences in reaction time and attentional bias However, there were no significant differences in the control group. Thus, it can be concluded that these two treatment models can be used to reduce the mentioned psychological abnormalities in students and help improve their mental health.